Personality Type and Language Learning Strategy use by University Students: Where the MBTI and SILL Intersect - Milne, Elizabeth Wendy (University of Waterloo, 2020)
This thesis explores the relationship between personality type, as defined by the Myers-Briggs Type Indicator® (“MBTI®”), and the learning strategies employed by learners enrolled in undergraduate foreign language courses at the University of Waterloo. The R.L. Oxford© Strategy Inventory for Language Learning (“SILL”) version 5.1, designed specifically for speakers of English learning a new language, will be used by participants to self-assess current learning strategies (Oxford, 1990). The quantitative portion of the study cross tabulates the data generated from these two electronically administered surveys in an attempt to identify clusters of personality types and learning strategies and determine if any statistically significant correlations between personality type and student learning strategies exist. This study could not prove a higher percentages of any particular type(s) tends to enrol in second language acquisition courses, nor that a corresponding or any set of preferred learning strategies are used. An exploratory research approach is taken for the qualitative portion of the study to examine the language used by participants when answering non-prompted open-ended questions. Specifically, keywords and common phrases from the responses are used to determine if they are predictive of an MBTI type preference. The language the participants used to respond to the short answer questions did not point toward any type preferences; however, a more detailed examination with larger writing samples may be warranted to confirm this finding.
Keywords: MBTI; SILL; language learning; learning strategies; personality type